CompTIA Linux+ XK0-004 : complete video course - Vugt, Sander van (LiveLessons (Indianapolis, Ind.), 2019)
CompTIA Linux+ has more than 20 hours of comprehensive video training so you have everything you need to prepare for the CompTIA Linux+ exam and also build a strong understanding of working with Linux. This title includes a copy of Linux Fundamentals LiveLessons. CompTIA Linux+ Complete Video Course has more than 20 hours of comprehensive video training covering all of the objectives on the CompTIA Linux+ exam. Expert author and trainer Sander van Vugt will walk you first through Linux basics with 10 hours of essential concepts in his Linux Fundamentals LiveLessons title. You will then get a deep dive into core Linux topics. This thorough and engaging training provides whiteboard concept teaching, live CLI work, screencast teaching, and hands-on labs, so you have everything you need to study for - and pass - the CompTIA Linux+ exam.